Changes in muscle strength in U19 soccer playersd during an annual training cycle - Lehnert, M.; Xaverova, Z.; De Ste Croix, M. (Journal of Human Kinetics, 2014)
The aim of the study was to investigate the seasonal variation in isokinetic strength of the knee flexors and extensors, and conventional (H/QCONV) and functional (H/QFUNC) hamstring to quadriceps strength ratios in highly trained adolescent soccer players. The players (n=11; age 17.8±0.3) were measured at the end of the competitive season (autumn), at the beginning and the end of pre-season (winter) and during the sixth week of a new competitive season. Isokinetic peak torque (concentric and eccentric) was measured at 60°•s-1 in a sitting position with the hip flexed at 100°. The testing range of motion was set from 10 - 90° of knee flexion. The players performed a set of five maximum repetitions for both the dominant and non-dominant leg. Statistically significant differences (p<0.001) between the four seasonal measurements were noted for peak torque of the dominant leg knee flexors in concentric muscle action only. A post hoc analysis revealed a statistically significant increase in peak torque from the 1st to the 4th measurement (p<0.001; d=0.692) and from the 2nd to the 4th (p<0.01; d=0.564). The differences in the changes of peak torque of the knee flexors and extensors depending on type of muscle action and tendencies found in the H/Q ratios throughout the annual training cycle indicate that strength assessment of the knee flexors and extensors and their balance throughout the annual training cycle could be beneficial for elite male adolescent soccer players both in terms of performance and risk of injury.